(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study was to find out the effect of Resistance training with and without swissball training on Explosive power of male basketball players .To achieve the purpose of the study, To achieve the purpose of the study, thirty male basketball players were randomly selected as subjects from Kalinga University Naya Raipur during the Inter- University basketball Camp held at Kalinga University in 2019. The age of the subjects were ranged between 18 to 25 years. There were three equal groups of 30 patients each in the before and post test random group design. The RT Group (n=10) was used as an experimental group in this study. Swiss ball resistance training (SBRT) was used in the second experimental group (n=10). Control group (n=10 CG) did not undergo any specific training programmed but there practiced the regular game. The following physical fitness parameters are explosive power. The analysis of covariance was used to analyze the significant difference, if any among the groups. Since, three groups were compared, whenever the obtained ‘F’ ratio for adjusted post test was found to be significant, the Scheffe’s test to find out the paired mean differences, if any. The 0.05 level of confidence was fixed as the level of significance to test the ‘F’ ratio obtained by the analysis of covariance, which was considered as an appropriate. The result of the study indicates due to training on explosive power has been improved significantly.